2011
DOI: 10.1097/mpg.0b013e31821b4b61
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Quantitative Estimation of Hepatic Steatosis in Children With NAFLD

Abstract: Background & Aims The diagnostic accuracy of hepatic ultrasonography for detection and grading of hepatic steatosis in children with suspected nonalcoholic fatty liver disease (NAFLD) remains poorly characterized. The aim of this study was to prospectively evaluate the clinical utility of ultrasonographic quantification of hepatic steatosis. Methods Our cohort consisted of 208 consecutive pediatric patients with biopsy-proven NAFLD. Hepatic ultrasonography was performed within 1-month of the liver biopsy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(223 citation statements)
references
References 22 publications
7
200
0
8
Order By: Relevance
“…Ultrasonographic evaluation was carried out by a pediatric radiologist with an experience in gastrointestinal US. The frequency of transducer for microconvex and linear (General Electric Logic 9) array was 5-8 and 10-14 MHz, respectively (Shannon et al 2011). Other causes of hepatic steatosis (including alcohol abuse, drugs, and genetic diseases if clinically indicated) were excluded in each patient.…”
Section: Patientsmentioning
confidence: 99%
“…Ultrasonographic evaluation was carried out by a pediatric radiologist with an experience in gastrointestinal US. The frequency of transducer for microconvex and linear (General Electric Logic 9) array was 5-8 and 10-14 MHz, respectively (Shannon et al 2011). Other causes of hepatic steatosis (including alcohol abuse, drugs, and genetic diseases if clinically indicated) were excluded in each patient.…”
Section: Patientsmentioning
confidence: 99%
“…NAFLD was diagnosed based on US data, and the severity of liver disease was not confirmed histologically. A recent study (34) showed that US is useful for quantifying hepatosteatosis and that its results can be strongly correlated with the grade of hepatosteatosis obtained by liver biopsy. In addition, US is ethically relevant, easily reproducible, and not associated with any complications, which are the major drawbacks associated with liver biopsy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, dyslipemia, and hyperuricemia may serve as guiding parameters for metabolic syndrome. 12,15,16 Waist circumference measurement (measured at the edge of the iliac crests) is an important anthropometric parameter to identify central fat accumulation and, if increased, it may predict the risk of insulin resistance and metabolic syndrome.…”
Section: Clinical Presentationmentioning
confidence: 99%